Intraoperative ultrasound in recurrent gliomas surgery: Impact on residual tumor volume and patient outcomes - Wang, Meiyao; Yu, Jin; Zhang, Jibo; Pan, Zhiyong; Chen, Jincao (Frontiers in Oncology, 2023)
BACKGROUND: Reoperation may be beneficial for patients with recurrent gliomas. Minimizing the residual tumor volume (RTV) while ensuring the functionality of relevant structures is the goal of the reoperation of recurrent gliomas. Intraoperative ultrasound (IoUS) may be helpful for intraoperative tumor localization, intraoperative real-time imaging to guide surgical resection, and postoperative evaluation of the RTV in the reoperation for recurrent gliomas. OBJECTIVE: To assess the effect of real-time ioUS on minimizing RTV in recurrent glioma surgery compared to Non-ioUS. METHODS: We retrospectively analyzed the data from 92 patients who had recurrent glioma surgical resection: 45 were resected with ioUS guidance and 47 were resected without ioUS guidance. RTV, Karnofsky Performance Status (KPS) at 6 months after the operation, the number of recurrent patients, and the time to recurrence were evaluated. RESULTS: The average RTV in the ioUS group was significantly less than the Non-ioUS group (0.27 cm3 vs. 1.33 cm3, p = 0.0004). Patients in the ioUS group tended to have higher KPS scores at 6 months of follow-up after the operation than those in the Non-ioUS group (70.00 vs. 60.00, p = 0.0185). More patients in the Non-ioUS group experienced a recurrence than in the ioUS group (43 (91.49%) vs. 32 (71.11%), p = 0.0118). The ioUS group had a longer mean time to recurrence than the Non-ioUS group (7.9 vs. 6.3 months, p = 0.0013). CONCLUSION: The use of ioUS-based real-time for resection of recurrent gliomas has been beneficial in terms of both RTV and postoperative outcomes, compared to the Non-ioUS group.